Middle‐term mortality and re‐bleeding after initial diverticular bleeding: A nationwide study of 365 mostly elderly French patients. Issue 1 (1st February 2017) - Lorenzo, Diane; Gallois, Claire; Lahmek, Pierre; Lesgourgues, Bruno; Champion, Christine; Charpignon, Claire; Faroux, Roger; Bour, Bruno; Remy, André‐Jean; Naouri, Chantal; Picon, Magali; Poncin, Eric; et al.
Abstract : Background and aims: The aim of this study was to determine the mortality and re‐bleeding rates, and the risk factors involved, in a cohort of patients with previous diverticular bleeding (DB). Methods: In 2007, data on 2462 patients with lower gastrointestinal (GI) bleeding were collected prospectively at several French hospitals. We studied the follow‐up of patients with DB retrospectively. The following data were collected: age, mortality rates and re‐bleeding rates, drug intake, surgery and comorbidities. Results: Data on 365 patients, including 181 women (mean age 83.6 ± 9.8 years) were available. The median follow‐up time was 3.9 years (IQR 25–75: 1.7–5.4). Of these, 148 patients died (40.5%). Among the 70 patients (19.2%) who had at least one re‐bleeding episode, nine died and three underwent surgical procedures. Anticoagulation and antiplatelet therapy was discontinued in 70 cases (19.2%). The independent risk factors contributing to mortality were age > 80 years (HR = 3.18 (2.1–4.9); p  < 0.001) and a Charlson comorbidity score > 2 (1.91 (1.31–2.79); p  = 0.003). Discontinuation of therapy was not significantly associated with a risk of death due to cardiovascular events. No risk factors responsible for re‐bleeding were identified, such as antiplatelet and anticoagulant therapy in particular. Conclusions: In this cohort, the rates of mortality and DB re‐bleeding after a median follow‐up time of 3.9 years were 19.2% and 40.5%, respectively. The majority of the deaths recorded were not due to re‐bleeding.